2020
DOI: 10.12741/ebrasilis.v13.e910
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of botanical extracts against Aphis craccivora Koch (Hemiptera: Aphididae) nymphs in Vigna unguiculata (L.) Walp

Abstract: The present study aimed to evaluate the insecticidal activity of hydroalcoholic plant extracts on Aphis craccivora Koch nymphs in cowpea. The experiments were carried out under greenhouse conditions in a randomized block design with five repetitions. Hydrated ethanol was used as a solvent in the botanical extract preparation. Cowpea plants were infested with five female adult aphids, eleven days after planting. After 48 hours, the adults were removed from the plants, leaving the recently bred nymphs. The evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Based on the results of the preliminary test with aqueous extract of A. montana leaves, it was observed that the 20% concentration caused 81.3% mortality, at the nymph stage, 24 h after the application of treatments by spraying, and this concentration was chosen for the other bioactivity tests on the cowpea aphid (Figure 1). Studies with aqueous extracts of the genus Annona on the biological cycle of Aphis craccivora have already been reported (Dutra et al, 2020). Sanches et al (2021) and Cruz-Estrada et al (2013), also found the toxic effect of aqueous extracts, including those of A.…”
Section: Resultsmentioning
confidence: 93%
“…Based on the results of the preliminary test with aqueous extract of A. montana leaves, it was observed that the 20% concentration caused 81.3% mortality, at the nymph stage, 24 h after the application of treatments by spraying, and this concentration was chosen for the other bioactivity tests on the cowpea aphid (Figure 1). Studies with aqueous extracts of the genus Annona on the biological cycle of Aphis craccivora have already been reported (Dutra et al, 2020). Sanches et al (2021) and Cruz-Estrada et al (2013), also found the toxic effect of aqueous extracts, including those of A.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, they demonstrated that plant-derived product based cotton seed, clove, and garlic oil and commercially plant extract based rosemary, cinnamon, clove oil, and garlic extract provided sufficient control of whitefly and green peach aphid up to 21 days after application. Moreover, Dutra et al (2020) used hydro-alcoholic plant extracts to control of A. craccivora nymphs on cowpea under greenhouse conditions. They reported that garlic Allium tuberosum leaf and A. sativum bulb extracts was recorded more than 50% efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Also, 40% garlic-based extract namely GC-mite was effective against the red spider mite, T. evansi on tomatoes under greenhouse and field conditions (Kithusi, 2005). Moreover, Dutra et al (2020) used garlic Allium tuberosum leaf and A. sativum bulb extracts to control of A. craccivora nymphs on cowpea under greenhouse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils can act as toxins, antifeedants, and repellents for many aphid species (Mossa, 2016). Many investigators reported the insecticidal effect of essential oils against A. craccivora (Dutra et al, 2020 andSayed et al, 2020). In earlier research, Abdul Kareem et al (1989) suggested the use of neem for rice before sowing to control two homopterous pests.…”
Section: Introductionmentioning
confidence: 99%